REFERENCES AND CONJUNCTIONS AS MARKERS OF PROPOSITIONAL RELATIONS IN DISCOURSE SEMANTICS - Harris Hermansyah Setiajid (Universitas Bandar Lampung, 2022)
Discourse is the most fundamental linguistic unit that is commonly used in daily life. To compose an effective discourse, one needs a mechanism for combining the discourse's propositions. The technique is referred to as a proposition relational marker. The tool's format, which includes references and conjunctions. The term